Structural Analysis of “Peanut & Sparky”: A Short Story by Arnie Lightning as A Way in Understanding Literature - Umar Fauzan (Journal of English Language Teaching and Linguistics, 2016)
This study aims at analyzing the structure of Arni Lightning’s  short story Peanut & Sparky plays an essential part in a literary work which explores the plot, setting, characters, conflict and other elements of the story. Instead of that, by conducting this analysis, it could make the narration comprehensible for the readers and also to catcth the meaning which the writer wants to convey. The short story Peanut & Sparky was published in April 2015 in America. This analysis captures the writer’s intention of fabricating the story through its premise,theme, character, moral value, setting. The study reveals that conducting structural analysis is supposed to be a good way in understanding literary works.Key words: Structural, analysis, Short Story,Literature